Metode Musyafahah Untuk Meningkatkan Kemampuan Membaca Al-Qur’an Siswa SMP-IT As-Salam Ambon - Husen Muhammad; Nur Khozin (LPPM IAIN Sorong, 2022)
Abstract: The purpose of this study was to determine the increase in the ability to read the Koran for SMP-IT As-Salam Ambon students using the deliberation method. This research is Classroom Action Research (CAR). The results showed that in the first cycle of 31 students it was found that the qualification score was